2019
DOI: 10.5194/angeo-37-129-2019
|View full text |Cite
|
Sign up to set email alerts
|

Spring and summer time ozone and solar ultraviolet radiation variations over Cape Point, South Africa

Abstract: The correlation between solar ultraviolet radiation (UV) and atmospheric ozone is well understood. Decreased stratospheric ozone levels which led to increased solar UV radiation levels at the surface have been recorded. These increased levels of solar UV radiation have potential negative impacts on public health. This study was done to determine whether the break-up of the Antarctic ozone hole has an impact on stratospheric columnar ozone (SCO) and resulting ambient solar UV-B radiation levels at Cape Point, S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
4
0
1
Order By: Relevance
“…However, a recent study found that the breakup of the polar vortex had only a small effect on UV radiation at Cape Town, South Africa (34° S). Elevated levels of UV radiation at this location were more frequently associated with low-ozone air masses of tropical origin [ 234 ].…”
Section: Variability In Uv Radiation and Trends From Observationsmentioning
confidence: 99%
“…However, a recent study found that the breakup of the polar vortex had only a small effect on UV radiation at Cape Town, South Africa (34° S). Elevated levels of UV radiation at this location were more frequently associated with low-ozone air masses of tropical origin [ 234 ].…”
Section: Variability In Uv Radiation and Trends From Observationsmentioning
confidence: 99%
“…Taking into account that there is no ground-based derived UV index for Santarém, in order to make a comparison and clarify which of the two satellite time series better represent the reality of the UVI variability in this area, the variation of the solar zenith angle (SZA) over the year for Santarém was plotted (Figure 3), so that it was possible to understand which series presents variability more in accordance with the variability of the SZA. The SZA is the angle measured from the surface between the Sun and a point directly above the observer (Du Preez, 2019;Cadet et al, 2020). Smaller SZAs results in greater solar flux reaching the Earth's surface, this happens more frequently around noon and during summer months (Wald, 2018).…”
Section: Uv Index Monthly and Seasonal Variabilitymentioning
confidence: 99%
“…Smaller SZAs results in greater solar flux reaching the Earth's surface, this happens more frequently around noon and during summer months (Wald, 2018). At larger SZAs (at dawn and dusk time), UVR is lower, as the path through the atmosphere is longer and results in more attenuation of UVR through the scattering and absorption by particles and gases in the atmosphere (Wald, 2018;Du Preez, 2019). At places within the Tropic of Capricorn the sun is at its peak twice a year and the stations register two annual maximums (Coariti, 2017).…”
Section: Uv Index Monthly and Seasonal Variabilitymentioning
confidence: 99%
“…Clouds result in large spatial and temporal variability of surface UVR radiation levels. To remove the effect of clouds on observed UVR, clear-sky days were determined using a clear-sky determination method [42,43]. To do so, three steps were used.…”
Section: Observed Uvb Data For Pretoriamentioning
confidence: 99%